Online Game Addiction and the Level of Depression Among Adolescents in Manila, Philippines - Ryan V. Labana; Jehan L. Hadjisaid; Adrian R. Imperial; Kyeth Elmerson Jumawid; Marc Jayson M. Lupague; Daniel C. Malicdem (University Library System, University of Pittsburgh, 2020)
Introduction: World Health Organization recognizes online game addiction as a mental health condition. The rise of excessive online gaming is emerging in the Philippines, with 29.9 million gamers recorded in the country. The incidence of depression is also increasing in the country. The current correlational analysis evaluated the association between online game addiction and depression in Filipino adolescents. Methods: A paper-and-pencil self-administered questionnaire assessing depression and online game addiction was distributed from August to November, 2018. The questionnaire included socio-demographic profiles of the respondents, and the 14-item Video Game Addiction Test (VAT) (Cronbach's α=0.91) and the Patient Health Questionnaire-9 (Cronbach's α=0.88) to determine levels of online game addiction and depression, respectively. Multiple regression analyses were used to test the association between depression and online game addiction. Results: Three hundred adolescents (59% males, 41% females) participated in the study. Fifty-three out of 300 respondents (12.0% males, 5.7% females) had high level of online game addiction as reflected in their high VAT scores. In this study, 37 respondents (6.7% males, 5.7% females) had moderately severe depression and 6 (2.0%) females had severe depression. Online game addiction was positively correlated with depression in this study (r=0.31; p<0.001). When multiple regression analysis was computed, depression was found to be a predictor of online game addiction (Coefficient=0.0121; 95% CI-8.1924 - 0.0242; p=0.05). Conclusion: Depression, as associated with online game addiction, is a serious threat that needs to be addressed. High level of online game addiction, as positively correlated to the rate of depression among adolescents in Manila, could potentially be attributed to the booming internet industry and lack of suffiicent mental health interventions in the country. Recommended interventions include strengthening depression management among adolescents and improving mental health services for this vulnerable population groups in schools and within the communities.